From Clicks to Violence: A Study on the Role of Social Media in Radicalization and Terrorism - Marizaldi, Deki; Pratama, Muhammad Herdi; Sulatiasto, Abipraya Guntur; Budiharso, Anaga (JURNAL AKTA, 2025)
This study aims to examine the role of social media in radicalization and terrorism. Social media has become an effective platform for extremist groups to spread their ideology, recruit members, and coordinate activities. The research highlights how extremist content is disseminated through social media, how these groups use the platforms to recruit and build communities, and how the narratives and propaganda they construct can influence individuals, especially those who are vulnerable. The impacts of radicalization through social media include changes in individual behavior and perspectives, social polarization, conflict, and an increased threat of terrorism. This study also discusses various prevention and countermeasures that can be implemented, such as counter-radicalization, deradicalization, and law enforcement.